Oil Extraction from Rice Bran with Various Solvents and Concentration of Crude Extract to Antioxidant Activity - Suryadinata, Arief (ALCHEMY, 2015)
Rice bran contains components such as oryzanol antioxidants, tocopherols, tocotrienols, phytosterols, polyphenols, and squalene. Oryzanol is a very powerful antioxidant and oryzanol is only found in rice bran oil. This research aims to know the antioxidant activity of the extract chloroform:methanol in the bran and find the endurance of antioxidant against a wide variety of pH and temperature. The method used is descriptive research through experimental tests in the laboratory. Samples taken from the side of rice mills in the form of bran and then macerated with chloroform: methanol. After that tested the antioxidant activity of the compounds made by the method of DPPH with various concentration 10, 20, 30, 40 and 50 ppm. Furthermore, the endurance test of antioxidant compounds at various pH and temperature using the best concentration of antioxidant compounds. Based on the results, rice bran oil extract concentration of 50 ppm has antioxidant activity of 4.69%. Average yield the highest antioxidant activity shown in heating conditions with a temperature of 30oC for 30 minutes is equal to 32.25%. As well as the highest antioxidant activity was also shown at pH 5 in the amount of 25.1%.Â Keywords: DPPH, Oryzanol, Rice bran